2002
DOI: 10.1136/gut.51.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Double blind, placebo controlled trial of the remission inducing and steroid sparing properties of an ICAM-1 antisense oligodeoxynucleotide, alicaforsen (ISIS 2302), in active steroid dependent Crohn's disease

Abstract: Background and aims: To evaluate the safety and efficacy of the intercellular adhesion molecule 1 (ICAM-1) antisense phosphorothioate oligonucleotide alicaforsen (ISIS 2302) in Crohn's disease. Methods: Active (Crohn's disease activity index (CDAI) 200-350), steroid dependent (prednisone 10-40 mg) Crohn's patients were randomised into three treatment groups: placebo versus ISIS 2302 (2 mg/kg intravenously three times a week) for two or four weeks. Patients were treated in months 1 and 3, with steroid withdrawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(109 citation statements)
references
References 36 publications
(28 reference statements)
2
102
1
4
Order By: Relevance
“…However, treatment with ISIS 2302 was judged to be ineffective and enrollment was terminated early [Schreiber et al 2001]. In the second trial, 299 patients in the US and Europe with moderately active steroid-dependent CD received an intensified regimen of ISIS 2302 (2 mg/kg IV three times per week) for up to 4 weeks or placebo [Yacyshyn et al 2002]. After a 1-month interval without treatment, the same treatment schedule was repeated.…”
Section: Vedolizumab/mln0002mentioning
confidence: 99%
“…However, treatment with ISIS 2302 was judged to be ineffective and enrollment was terminated early [Schreiber et al 2001]. In the second trial, 299 patients in the US and Europe with moderately active steroid-dependent CD received an intensified regimen of ISIS 2302 (2 mg/kg IV three times per week) for up to 4 weeks or placebo [Yacyshyn et al 2002]. After a 1-month interval without treatment, the same treatment schedule was repeated.…”
Section: Vedolizumab/mln0002mentioning
confidence: 99%
“…Oligonucleotides based on the phosphorothioate backbone are highly promising compounds for therapeutic antisense applications. The first of these antisense oligonucleotides was admitted to market in 1998 and further RNase H activating phosphorothioate oligonucleotides are currently in various stages of clinical trial [3,[19][20][21]. Investigation of the dissociation pattern of phosphorothioate, and phosphodiester oligodeoxyribonucleotides in gas-phase revealed that both backbone modifications yield the same types of fragment ions [22,23].…”
mentioning
confidence: 99%
“…Only 2 of 60 (3.3%) ISIS-2302-treated and none of placebo treated patients reached the primary endpoint; steroid free remission at week 14. A more recent study by Yasyshyn et al [44] was also negative. A total of 299 patients were enrolled; with a mean baseline CDAI of 276 and steroid dose of 23 mg/day.…”
Section: Integrin Receptor Blockersmentioning
confidence: 79%